Behaviour visualization for malicious-attacker node collusion in MANET based on probabilistic approach - Olanrewaju, Rashidah Funke; Khan, Burhan ul Islam; Mir, Roohie Naaz; Shah, Asadullah (Open Science, 2015)
Inspite of wide range of exploration towards the mitigation techniques for malicious nodes in past few years, the effective solution for addressing the behavioral patterns of malicious nodes are still largely un-found. One of the most challenging dynamics related to this issue is an effective visualization of malicious nodes will never adopt any strategies in which has fairer chances of getting detected, hence, they will perform much confused behavior based on which it is almost difficult to identify whether it is regular node or malicious node. The current paper accentuates the potentials of game theory considering mutli-attacker collusion as the new enhancement that can effectively represent the various unpredictable actions of node cooperation, node declination, node attacks, as well as node reporting that can model the tactical profiling of various mobile nodes.